2022
DOI: 10.48550/arxiv.2208.01612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comprehensive Study on Galaxies at z~9-16 Found in the Early JWST Data: UV Luminosity Functions and Cosmic Star-Formation History at the Pre-Reionization Epoch

Abstract: We conduct a comprehensive study on dropout galaxy candidates at z ∼ 9 − 17 using the first 90 arcmin 2 JWST/NIRCam images taken by the early release observations (ERO) and early release science (ERS) programs. With the JWST simulation images, we find that a number of foreground interlopers are selected with a weak photo-z determination (∆χ 2 > 4). We thus carefully apply a secure photo-z selection criterion (∆χ 2 > 9) and conventional color criteria with confirmations of the ERO NIRSpec spectroscopic redshift… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(100 citation statements)
references
References 112 publications
(197 reference statements)
6
93
0
1
Order By: Relevance
“…CEERS-1749 was also recently reported by Donnan et al (2022, see also Harikane et al 2022a), in their search for z > 10 candidates across the JWST ERS data, as lying at z = 16.6. They infer a slightly lower mass of log(M /M ) = 9.0 ± 0.4.…”
Section: Ceers-1749 At Z ∼ 17supporting
confidence: 59%
See 3 more Smart Citations
“…CEERS-1749 was also recently reported by Donnan et al (2022, see also Harikane et al 2022a), in their search for z > 10 candidates across the JWST ERS data, as lying at z = 16.6. They infer a slightly lower mass of log(M /M ) = 9.0 ± 0.4.…”
Section: Ceers-1749 At Z ∼ 17supporting
confidence: 59%
“…This paper follows an earlier analysis of Naidu et al (2022a), who identified the most luminous galaxy candidates in the existing ERS imaging data, based on optical non-detection criteria and photometric redshift measurements using the EAZY code (Brammer et al 2008). As first noted in that paper, the CEERS field revealed a seemingly reliable, but extremely luminous galaxy candidate with photometric redshift at z = 16.6 ± 0.1 (see also Donnan et al 2022;Harikane et al 2022a). Given its extraordinary luminosity, if confirmed to lie at z ∼ 17, this source deserved special attention and analysis.…”
Section: Selection Of Luminous High-redshift Galaxy Candidatesmentioning
confidence: 61%
See 2 more Smart Citations
“…• Extinguished high-𝑧 star-forming sources (8 < 𝑧 < 13): the daily recording of the farthest objects with JWST is currently providing candidates up to 𝑧 ∼ 17 (e.g. Harikane et al 2022). These sources are consistent with primordial young star forming galaxies, with a negligible dust content.…”
Section: Nature Of the F444w Sources Without A F200w Counterpartmentioning
confidence: 99%